The diffraction detector for the EMD of the CSNS. (14th December 2021) - Yu, Q.; Tang, B.; Huang, C.; Wei, Y.; Chen, S.; Tang, M.; Wang, X.; Xu, H.; Sun, Z.; Wei, G.
Abstract: On 23rd August 2018, the China Spallation Neutron Source (CSNS) located in Dongguan operated 4 neutron instruments. In the future, twenty neutron spectrometers will be built to provide multidisciplinary platforms for scientific research by national institutions, universities, and industries. Engineering Material Diffractometer (EMD), which will be used for strain measurements in engineering materials and components, will be constructed at the Beamline 8 in 2022. A novel thermal neutron detector, which will comply with the requirements of EMD application, is being developed. This detector will consist of 6 LiF/ZnS(Ag) scintillation screens, wavelength shifting fiber (WLSF) arrays, a silicon photomultiplier (SiPM) and Application Specific Integrated Circuit (ASIC) read-out electronics. Each scintillation screen will be inclined with respect to the incident neutron beam at a grazing angle θ = 17°. Such geometry will not only improve the spatial resolution of detectors but also the neutron detection efficiency. The prototype of detector module has been tested at the neutron Beamline 20 at the CSNS. The experimental results obtained for this prototype illustrate that the pixel size of detector module is 3 mm and the detection efficiency exceeds 40% at the neutron wavelength of 1 Å. Based on these results, we design and manufacture the final version of the detector for the EMD application, which is characterized by low power consumption, highly integrated and easy to install. 70 such detectors will be installed till the end of 2021.